1988
DOI: 10.1152/ajpgi.1988.255.5.g685
|View full text |Cite
|
Sign up to set email alerts
|

Action of the cholecystokinin antagonist L364,718 on gastric emptying in the rat

Abstract: Cholecystokinin (CCK) is a potent inhibitor of gastric emptying. We have examined the effects of a novel potent peripheral CCK receptor antagonist (L364,718) on the action of endogenous and exogenous CCK octapeptide (CCK-8) on gastric emptying in the rat. In conscious gastric fistula rats, the recovery of liquid test meals of 3.0 ml (containing phenol red as a dilution marker) was determined over periods up to 8 min. Compared with saline, gastric emptying of solutions of peptone (4.5%), 50 mM HCl, and hyperosm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
29
0
2

Year Published

1989
1989
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 0 publications
3
29
0
2
Order By: Relevance
“…The two receptors display about 50% sequence homology (Silvente-Poirot et al 1993;Kopin et al 1992). The cholecystokinin-A receptor mediates the cholecystokinin-8~-induced exocrine pancreatic secretion and the cholecystokinin-8s induced inhibition of gastric emptying (Green et al 1988). Monitoring gastric emptying in mice is a useful and simple way to screen the effect of cholecystokinin receptor ligands on cholecystokinin-A receptors (Lotti e f al.…”
Section: Discussionmentioning
confidence: 99%
“…The two receptors display about 50% sequence homology (Silvente-Poirot et al 1993;Kopin et al 1992). The cholecystokinin-A receptor mediates the cholecystokinin-8~-induced exocrine pancreatic secretion and the cholecystokinin-8s induced inhibition of gastric emptying (Green et al 1988). Monitoring gastric emptying in mice is a useful and simple way to screen the effect of cholecystokinin receptor ligands on cholecystokinin-A receptors (Lotti e f al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seemed worthwhile to establish an appropriate animal model to test compounds known to release endogenous CCK for their ability to slow gastric emptying and improve postprandial hyperglycaemia in NIDDM. Camostat inhibited gastric emptying in conventional, non-diabetic rats via a CCK-dependent mechanism [10], but this has not been studied in rat models of IDDM or NIDDM. Furthermore, camostat stimulates secretin release in the rat [9], and secretin inhibits gastric emptying in conventional, nondiabetic rats [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the effect of treatment with a synthetic trypsin inhibitor (camostat), on gastric emptying of glucose and postprandial hyperglycaemia was determined. Camostat is a strong stimulant of CCK and secretin release [8,9] and an inhibitor of gastric emptying [10] in rats.…”
mentioning
confidence: 99%
“…Alternatively, it is possible that higher doses ofMK-329 might demonstrate an acceleration ofgastric emptying if the CCK receptors involved were different in some way from those mediating gallbladder contraction. This is unlikely, however, as animal studies have revealed MK-329 to be a potent antagonist of CCK-induced inhibition of gastric emptying (8,25,26). Since gastric emptying and CCK release are regulated by various properties of a meal, including nutrient composition, it is also possible that an alteration of gastric emptying with MK-329 may be demonstrable with other diets.…”
Section: Discussionmentioning
confidence: 99%